Mechanism of Liraglutide Regulating the Expression of PI3K/AKT/NF-KB Pathway-related Proteins on Nonalcoholic Fatty Liver Disease - Sang, Yao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Background and Objective: GLP-1RAs can effectively prevent hepatic steatosis. It was to investigate the mechanism by which the GLP-1RA Liraglutide ameliorates non-alcoholic fatty liver disease (NAFLD) and its impact on PI3K/AKT/NF-κB pathway. Materials and Methods: eight-week-old, clean-grade male C57BL/6J mice were assigned to Normal group (NG, fed standard chow), NAFLD group (high-calorie, high-cholesterol), and Liraglutide group (LG, high-calorie, high-cholesterol for 12 weeks + Liraglutide treatment at 1 mg/kg). Serum samples were collected from the mice to assess changes in glucose and lipid metabolism and liver function (LF) indicators. Histopathological changes in liver tissues (LTs) were visualized. Real-time quantitative PCR measured expression levels (ELs) of inflammatory genes in LTs. Western blotting was conducted to detect EL of proteins related to PI3K/AKT/NF-κB pathway in LTs. Results: NAFLD group exhibited markedly elevated levels of blood glucose (BG), blood lipids, and LF indicators relative to NG. Histopathological examination revealed increased scores for steatosis, lobular inflammation, and hepatocellular ballooning. The ELs of inflammatory genes IL-1β, TNF-α, and NF-κB p65 in LTs, were greatly elevated (P